Pools of Silicon in Soils and their Contribution to Rice - and N.B. Prakash, Pallavi T. (Journal of the Indian Society of Soil Science, 2019)
Five major pools of silicon (Si) such as mobile Si, adsorbed Si, Si bound to organic matter, Si occluded in pedogenic oxides/hydroxides and amorphous Si were extracted from three soils namely one each from low, medium and high categories of plant available Si using a sequential extraction method. Different pools of Si extracted from soils were in the order of amorphous Si > occluded Si > organic Si > adsorbed Si and mobile Si. The mobile Si and adsorbed Si pools were the smallest pools of Si and ranged from 14.4 to 44.6 mg kg-1 and 4.9 to 89.4 mg kg-1, respectively. The content of organic Si and occluded Si ranged from 234 to 619 mg kg-1 and 476 to 1989 mg kg-1, respectively. Irrespective of the soils, amorphous Si was found to be the largest pool of Si ranging from 8019 to 16667 mg kg-1. Among different pools of Si, organic Si pool showed significant positive correlation with plant available Si while other pools had non-significant. A pot culture experiment was conducted using bulk soil samples with rice as test crop for a period of 60 days, and Si content and its uptake by rice was determined. Typic Rhodustalfs which is medium in plant available Si showed higher Si content (7.0%) and uptake (106 mg pot-1) compared to Chromic Haplusterts having high plant available Si. The correlation analysis to know the contribution of different Si pools to Si uptake by rice revealed that occluded, mobile, amorphous and adsorbed pools as the major contributors of Si to rice.